If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 144 + -5x = 6x + -9 Reorder the terms: 144 + -5x = -9 + 6x Solving 144 + -5x = -9 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 144 + -5x + -6x = -9 + 6x + -6x Combine like terms: -5x + -6x = -11x 144 + -11x = -9 + 6x + -6x Combine like terms: 6x + -6x = 0 144 + -11x = -9 + 0 144 + -11x = -9 Add '-144' to each side of the equation. 144 + -144 + -11x = -9 + -144 Combine like terms: 144 + -144 = 0 0 + -11x = -9 + -144 -11x = -9 + -144 Combine like terms: -9 + -144 = -153 -11x = -153 Divide each side by '-11'. x = 13.90909091 Simplifying x = 13.90909091
| -19-3x=5-9x | | 15x+2=13x-8 | | 5n-11=2n+4 | | 2x-7=10x-5 | | 66*78x=78*9x | | 5+n=15 | | 88*98=x+18 | | 1+x^5=10 | | 5x^2-20=x^2+80 | | 6(x^2-1)=18 | | 6+(5xn)=16 | | t*t+t=2000 | | k^2+2k=0 | | 1.1136=1.02*1.03*(1+x) | | x^5=9 | | (1+x)=1.02*1.03*1.02 | | t*t*t+t=2000 | | 49-6x=12x+21 | | (1+x)=1.015*1.0280 | | (1+x)=1.015*1.280 | | ln(x+6)+ln(2x)=ln(2) | | X^2+16=16 | | 1.1=1.015*1.05419*(1+x) | | 1.07=1.015*(1+x) | | (1+x)=1.023*1.030 | | -16x-5x=12-9x | | (1+x)=1.019*1.03 | | (1+x)=1.028*1.022*1.04 | | 114-6x=2x+18 | | 1.06=1.022*(1+x) | | 1.07=1.03*1.02*(1+x) | | 0.5*x^3+x^2-10*x+12=0 |